Ramadan fasting and diabetes in adolescents and children: A narrative review - Beshyah, Salem; Habeb, Abdelhadi; Deeb, Asma; Elbarbary, Nancy (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Although children in general and patients with type 1 diabetes mellitus, in particular, are exempted from fasting during Ramadan, many elect to observe the fast. There is a sizeable amount of opinion and research data that warrants revisiting. This is a narrative nonsystematic review to explore the views and supporting data on Ramadan fasting and to examine the safety of fasting and its impact on diabetes control and management in children and adolescents. The key areas covered include epidemiology, the physiology of fasting, risk stratification, counseling strategy, nutrition advice, insulin therapy adjustment with a particular focus on multiple injection regimen, and insulin pump therapy. Findings from various studies and expert opinions were appraised and presented to illustrate points of agreements and differences. This review should enhance knowledge and form the basis to clear some doubts and differences of opinions surrounding the issue of diabetes and Ramadan fasting in young people. It should also empower healthcare professionals to develop consensus based on the most up-to-date advice and the best possible support to patients and families regarding fasting during Ramadan.
Keywords: Adolescents; children; diet; fasting; hyperglycemia; hypoglycemia; insulin; metabolism; Ramadan; technology; type 1 diabetes